Application Of The Recitation Method To Improve Mathematics Learning Outcomes For Second Grade Students Of SD Negeri 0701 Rotan Sogo - Nur Hamidah Hasibuan (Indonesian Journal of Basic Education, 2022)
This research is a classroom action research to understand (1) the application of recitation in students' mathematics learning, and (2) the improvement of multiplication and division teaching materials. Using recitation to see the added value of student learning outcomes at SD Negeri 0701 Rotan Sogo Class II. The research tool used is the Learning Implementation Observation Sheet, Student Activity Observation Sheet and Student Learning Outcomes Test. The subjects of this study were second grade students of SD Negeri 0701 Rotan Sogo, totaling 21 students. This research was carried out in two cycles with four stages, namely: 1) planning, 2) action/implementation, 3) observation, 4) reflection. The results of data analysis that has been carried out and the teaching and learning process carried out have resulted in good student learning outcomes and increased in the application of the method. As a result of the first round of research, the data showed that of the 21 students in the second grade, 14 students completed the study, the mastery rate was 67%. As a result of the second round of research, the data showed an increase of 20 students and a completion rate of 95% of the 21 active students. Based on the results of the research that has been done, this study concludes that the use of the recitation method on multiplication and division material can improve mathematics learning outcomes for second grade students of SD Negeri 0701 Rotan Sogo. This is manifested as an improvement in the learning process and an increase in student achievement. Keywords: learning outcomes, memorization method, multiplication and division